PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD - Rama Medi Kesuma; Hetilaniar; Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low science learning outcomes among fifth-grade elementary school students indicate the need for innovation in learning models that can enhance students' understanding and engagement in the learning process. The Index Card Match learning model is one alternative that can be applied to address this problem. This study aims to determine the effect of the Index Card Match learning model on science learning outcomes of fifth-grade elementary school students. This study used an experimental method, namely True Experimental Design with a Posttest-Only Control Design. The sample in this study consisted of students from classes V.B and V.D, totaling 61 students, selected using Simple Random Sampling technique. Based on the hypothesis test conducted by the researcher using the Independent Sample T-Test, the calculated t value = 7.217 with a t table value = 1.671 at a significance level of 0.05. Thus, after examining the t-test results, it can be stated that Ha is accepted and Ho is rejected because the calculated t value > t table value (7.217 > 1.671). It can be concluded that there is an effect of the Index Card Match learning model on science learning outcomes of fifth-grade Elementary School Students.